2010
DOI: 10.1038/hr.2010.105
|View full text |Cite
|
Sign up to set email alerts
|

Essential fatty acids and their metabolites in the context of hypertension

Abstract: H ypertension is associated with an increase in peripheral vascular resistance, insulin resistance, endothelial dysfunction and enhanced activity of the sympathetic nervous system. 1 The condition causes morbidity and mortality. Hence, understanding its pathobiology is necessary to develop effective strategies for both prevention and management.There is increasing evidence that nutritional factors and type and level of fat in the diet are critical in the pathogenesis of essential hypertension. 2 Earlier, Weis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Similar to their beneficial action in STZ-induced Type 1 DM and diet-induced Type 2 DM, LXs, Rvs, protectins and nitrolipids are likely to be useful in the prevention and management of other inflammatory conditions, such as lupus, rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis, diabetic retinopathy and age-related macular degeneration [37,124,135,[140][141][142][143][144][145][146][147][148][149][150][151][152]. It is likely that all diseases in which low-grade systemic inflammation play a significant role, such as obesity, nonalcoholic fatty liver disease, hypertension, atherosclerosis, hyperlipidemia, CHD, depression, schizophrenia, Alzheimer's disease, aging, osteoporosis, Huntington's disease, polycystic ovarian syndrome, dermatitis, psoriasis, glomerulonephritis of different etiologies, scleroderma and other collagen vascular diseases may be due to deficiency of cyto protective LXs, Rvs, protectins, MaRs and nitrolipids [37,124,136,[141][142][143][144][145][146][147][148][149][150][151][152].…”
Section: Pufas Lxs Rvs Mars and Nitrolipids In Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to their beneficial action in STZ-induced Type 1 DM and diet-induced Type 2 DM, LXs, Rvs, protectins and nitrolipids are likely to be useful in the prevention and management of other inflammatory conditions, such as lupus, rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis, diabetic retinopathy and age-related macular degeneration [37,124,135,[140][141][142][143][144][145][146][147][148][149][150][151][152]. It is likely that all diseases in which low-grade systemic inflammation play a significant role, such as obesity, nonalcoholic fatty liver disease, hypertension, atherosclerosis, hyperlipidemia, CHD, depression, schizophrenia, Alzheimer's disease, aging, osteoporosis, Huntington's disease, polycystic ovarian syndrome, dermatitis, psoriasis, glomerulonephritis of different etiologies, scleroderma and other collagen vascular diseases may be due to deficiency of cyto protective LXs, Rvs, protectins, MaRs and nitrolipids [37,124,136,[141][142][143][144][145][146][147][148][149][150][151][152].…”
Section: Pufas Lxs Rvs Mars and Nitrolipids In Other Diseasesmentioning
confidence: 99%
“…It is likely that all diseases in which low-grade systemic inflammation play a significant role, such as obesity, nonalcoholic fatty liver disease, hypertension, atherosclerosis, hyperlipidemia, CHD, depression, schizophrenia, Alzheimer's disease, aging, osteoporosis, Huntington's disease, polycystic ovarian syndrome, dermatitis, psoriasis, glomerulonephritis of different etiologies, scleroderma and other collagen vascular diseases may be due to deficiency of cyto protective LXs, Rvs, protectins, MaRs and nitrolipids [37,124,136,[141][142][143][144][145][146][147][148][149][150][151][152]. It is suggested that in conditions such as hypertension, schizophrenia, depression, Alzheimer's disease and Huntington's disease, PUFAs, LXs, Rvs, protectins and MaRs may act not only on peripheral tissues, but also on specific areas of the brain, such as the hypothalamus.…”
Section: Pufas Lxs Rvs Mars and Nitrolipids In Other Diseasesmentioning
confidence: 99%
“…Previously, we showed that PUFAs and their metabolites play a critical role in the pathobiology of hypertension, pre-eclampsia, type 2 diabetes mellitus and metabolic syndrome [14,17,18,[22][23][24][25][26][27][28][29][30][31][32][33][34] . We, previously showed that AA prevents chemical-induced type 1 and type 2 diabetes, partly, due to its conversion to anti-inflammatory LXA4, [17,18] implying that the precursor PUFAs need to be converted to their specific anti-inflammatory metabolites to produce their beneficial actions.…”
Section: Interaction(s) Among Ang-ii Cytokines Ros and Pufas And Thmentioning
confidence: 99%
“…2 -, H 2 O 2 , lipid peroxides, NADPH oxidase, ACE activity, and myeloperoxidase activity, and decreased half-life and/or concentrations of PGI 2 and endothelial nitric oxide. 2,12 It is worthwhile to investigate whether these abnormalities are present in the o-3-deficient hypertension model of Begg et al 22 Low-grade systemic inflammation, as evidenced by enhanced plasma levels of interleukin-6 (IL-6), tumor necrosis factor-a (TNF-a) and high-sensitive CRP (hs-CRP), occurs in patients with hypertension. [34][35][36][37][38] Begg et al 22 have not measured plasma cytokines and hs-CRP levels in the o-3-deficient hypertensive animal model to know whether low-grade systemic inflammation is present.…”
mentioning
confidence: 99%
“…This is especially true in the light of the fact that increases in peripheral vascular resistance, insulin resistance and endothelial dysfunction and enhanced activity of the sympathetic nervous system are observed in obesity, type 2 diabetes mellitus and hypertension. [2][3][4][5][6][7][8][9][10][11] Hypertension is characterized by an increase in peripheral vascular resistance that could be attributed to the loss or decrease in endothelium-dependent vasodilation. The endothelium produces vasoactive factors such as prostacyclin (PGI 2 ), nitric oxide (NO), endothelium-derived hyperpolarizing factor, endothelin and prostaglandin E 1 (PGE 1 ).…”
mentioning
confidence: 99%